Television in the age of radio: modernity, imagination, and the making of a medium - Philip W. Sewell (Rutgers University Press, 2014)
Pulp publishing mogul Hugo Gernsback kicked off the June 1927 issue of Radio News with an editorial proclaiming, â€œWith the official recognition of Television by the Radio Commission, as well as the actual successful demonstration early in April by the American Telegraph and Telephone Co., it may be said that television has finally arrived.â€1 This was not televisionâ€™s first moment of arrival, and it was far from the last. Gernsbackâ€™s pronouncement and the editorial that followed do, however, point to some significant matters. First, that the United Statesâ€™ most widely read radio magazine and its editor- in- chief were heralding televisionâ€™s arrival several decades before it became a domestic commonplace testifies to a long period during which television existed as an object of conversation and imagination rather than a device in the home for (most of) the public. Second, the variance in capitalization between the first and second uses of the word television may be a sign of lax or eccentric copyediting, but it also hints at an uncertainty about usage that was in fact typical of articles about TV in the 1920s. Third, that Gernsback framed this arrival in terms of corporate display and governmental sanction suggests the matrix of institutional claims that would be made on and for the medium. Finally, since this was but one of many arrivals, Gernsbackâ€™s declaration indicates that what credibly constituted television and its moment of accomplishment and recognition was subject to change and dispute. All of these circumstances stem from the roles that culture and languageâ€” particularly as manifested in systems of authority and evaluationâ€” play in making and managing a social, technical, and economic phenomenon such as television. In the case of early television those roles were played on a number of stages as individuals and institutions thought and talked about television. This book explores the very real impact that language and culture have on our world and how we live in it, taking as its case study the role that imagination played in effecting television as a technology, industry, and medium in the United States. In particular, it focuses on the ways in which culture shaped the understandings of and aspirations for television in the period from the mid- 1920s to the late 1940s. Those knowledges and hopes matter not only because they worked to coordinate a host of human activities that were crucial to the development of television but also because they demonstrate some of the ways in which people made sense of and a place for themselves in industrialized modernity.